2012
DOI: 10.1371/journal.pone.0043217
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Relative Sensitivity of the Comparative Tuberculin Skin Test in Tuberculous Cattle Herds Subjected to Depopulation

Abstract: Bovine tuberculosis (bTB) is one of the most serious economic animal health problems affecting the cattle industry in Great Britain (GB), with incidence in cattle herds increasing since the mid-1980s. The single intradermal comparative cervical tuberculin (SICCT) test is the primary screening test in the bTB surveillance and control programme in GB and Ireland. The sensitivity (ability to detect infected cattle) of this test is central to the efficacy of the current testing regime, but most previous studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…In addition, it has been recently showed that the genetic background of the animal can also influence the reaction to tuberculin (Amos et al, 2013). The standard TST is estimated to be able to detect around 40-80% of infected animals (Francis et al, 1978apud Monaghan et al, 1994Karolemeas et al, 2012). Clearly, there is an urgent need form significant improvement on the test, so that it could be used with more confidence for enforcing the 'test-andslaughter' policy, reducing the number of false positive, as well as false negative results.…”
Section: Immunological Diagnosismentioning
confidence: 99%
“…In addition, it has been recently showed that the genetic background of the animal can also influence the reaction to tuberculin (Amos et al, 2013). The standard TST is estimated to be able to detect around 40-80% of infected animals (Francis et al, 1978apud Monaghan et al, 1994Karolemeas et al, 2012). Clearly, there is an urgent need form significant improvement on the test, so that it could be used with more confidence for enforcing the 'test-andslaughter' policy, reducing the number of false positive, as well as false negative results.…”
Section: Immunological Diagnosismentioning
confidence: 99%
“…One caveat, however, is that the initial disclosing SICCT skin test is not 100% sensitive. Indeed, SICCT test sensitivities in different countries and settings are reported to range from 75% to 95% (15,16), with a recent study estimating the relative SICCT test sensitivity in Great Britain as 85% (95% CI, 78% to 91%) or 81% (95% CI, 70% to 89%) for the severe or standard interpretation, respectively (17). Thus, in the serial testing scenario, it is possible that truly M. bovisinfected animals may be missed by the initial skin test and not subjected to the DIT.…”
Section: Discussionmentioning
confidence: 99%
“…The tuberculin skin test is effective in the early detection of pre-clinical cases of M. bovis infection in cattle. This allows the rapid removal of infected animals limiting transmission of the disease and eradication of bovine tuberculosis from many countries [18] . However, a few number of ancillary tests are being used, or are currently validated.…”
Section: Discussionmentioning
confidence: 99%